2022
DOI: 10.1073/pnas.2202172119
|View full text |Cite
|
Sign up to set email alerts
|

Seed DNA damage responses promote germination and growth inArabidopsis thaliana

Abstract: The desiccated, quiescent state of seeds confers extended survival of the embryonic plant. However, accumulation of striking levels of genome damage in quiescence impairs germination and threatens plant survival. The mechanisms by which seeds mitigate this damage remain unclear. Here, we reveal that imbibed Arabidopsis seeds display high resistance to DNA damage, which is lost as seeds advance to germination, coincident with increasing cell cycle activity. In contrast to seedlings, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…When considering the types of cellular mortality, IR induced the enhanced accumulation of programmed cell death (PCD) and necrotic nuclei in Col0, while these were more pronounced in the sog1 mutant gene in the absence of stress ( Figure 6 c). These results prove once more that the SOG1 gene deficiency is strongly correlated with defects in DNA repair activation and PCD induction [ 49 , 92 , 93 , 94 ]. When looking at the gene expression data, the first observation that can be made in our system is that the TDP1β gene seems to be more expressed in the sog1 mutant compared to the Col0 line in the absence of IR treatment, whereas the TDP1α gene is similarly expressed in both genotypes ( Figure 6 d, CTRL samples).…”
Section: Resultsmentioning
confidence: 54%
“…When considering the types of cellular mortality, IR induced the enhanced accumulation of programmed cell death (PCD) and necrotic nuclei in Col0, while these were more pronounced in the sog1 mutant gene in the absence of stress ( Figure 6 c). These results prove once more that the SOG1 gene deficiency is strongly correlated with defects in DNA repair activation and PCD induction [ 49 , 92 , 93 , 94 ]. When looking at the gene expression data, the first observation that can be made in our system is that the TDP1β gene seems to be more expressed in the sog1 mutant compared to the Col0 line in the absence of IR treatment, whereas the TDP1α gene is similarly expressed in both genotypes ( Figure 6 d, CTRL samples).…”
Section: Resultsmentioning
confidence: 54%
“…Our previous work found that seeds were surprisingly resistant to X-ray induced DNA damage [ 16 ]. In particular, seeds maintained post-germinative growth after irradiation, with levels of programmed cell death (PCD) that were both delayed and attenuated relative to irradiated seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, genome maintenance mechanisms in plant cells are important not only for growth and development, but also in preserving the longer term stability of plant germplasm at the level of populations and species. Previously we demonstrated that experimental application of stresses to seeds, including X-irradiation or accelerated ageing (at 35°C and 83% relative humidity), resulted in PCD in early post-germination [ 16 ]. We hypothesised that similar effects occur in natural seed ageing and that cell death persists throughout seedling establishment, indicative of genome instability carried over from DNA damage incurred in the seed.…”
Section: Introductionmentioning
confidence: 99%
“…Even the NPR1-independent SAR induction via the ‘Dong-pathway’ requires SA as the DNA-damaging agent. Moreover, most studies assign partly overlapping, additive or even redundant functions to ATM and ATR ( 162 , 163 ), mainly because both kinases signal through the shared SUPPRESSOR OF GAMMA RESPONSE 1 (SOG1) ( 80 , 139 , 164 , 165 ). With exception of the sterility of double mutants of atm and atr ( 163 ), it seems difficult to envision a strictly ATM – and ATR-dependent process as it is indicated by our data for the DNA-induced increased in SA ( Figure 4C ).…”
Section: Discussionmentioning
confidence: 99%